2021
DOI: 10.1155/2021/6671129
|View full text |Cite
|
Sign up to set email alerts
|

Wild Bitter Melon Extract Regulates LPS-Induced Hepatic Stellate Cell Activation, Inflammation, Endoplasmic Reticulum Stress, and Ferroptosis

Abstract: The activation of hepatic stellate cells (HSCs) is a key component of liver fibrosis. Two antifibrosis pathways have been identified, the reversion to quiescent-type HSCs and the clearance of HSCs through apoptosis. Lipopolysaccharide- (LPS-) induced HSCs activation and proliferation have been associated with the development of liver fibrosis. We determined the pharmacological effects of wild bitter melon (WM) on HSC activation following LPS treatment and investigated whether WM treatment affected cell death p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 100 publications
0
18
0
Order By: Relevance
“…In our previous study, we proposed that WBM has a protective effect against spinal cord injury (SCI) via a CDGSH iron sulfur domain 2 (CISD2)-dependent mechanism in SH-SY5Y human neuroblastoma cell lines and SCI mouse models [ 14 ]. Moreover, results also indicated that WBM alleviated lipopolysaccharide-induced hepatic stellate cell (HSC) activation and proliferation via the regulation of endoplasmic reticulum (ER) stress and ferroptosis [ 15 ]. Huang et al reported that WBM exerts an anti-inflammatory effect on Propionibacterium acnes-induced skin inflammation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we proposed that WBM has a protective effect against spinal cord injury (SCI) via a CDGSH iron sulfur domain 2 (CISD2)-dependent mechanism in SH-SY5Y human neuroblastoma cell lines and SCI mouse models [ 14 ]. Moreover, results also indicated that WBM alleviated lipopolysaccharide-induced hepatic stellate cell (HSC) activation and proliferation via the regulation of endoplasmic reticulum (ER) stress and ferroptosis [ 15 ]. Huang et al reported that WBM exerts an anti-inflammatory effect on Propionibacterium acnes-induced skin inflammation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory cytokines are key players of fibrotic mediators and are associated with worse prognosis of the inflammatory liver disease [26]. The CCl 4 administration led to a rise in the level of pro-inflammatory mediators such as TNF-α, IL-6, IL-8, and IFN-γ (Figure 3A-D).…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is an endotoxin made up of a polysaccharide and induces inflammation in various organs, including the liver, kidney, and brain, as well as murine macrophages and HSCs. Most of the toxicities observed in LPS-induced injury have been attributed to toxic mediators produced by activated cells, including TNF-α, iNOS, IL-1β, IL-6, ZEB-2, PTEN, and other pro-inflammatory molecules [25][26][27][28][29]. However, to the best of our knowledge, there was no previous detailed information about the effects of orientin on LPS-mediated pro-inflammatory responses on HSCs, as well as its anti-inflammatory activity towards CCl 4 -induced liver inflammation on experimental mice.…”
Section: Introductionmentioning
confidence: 99%
“…For one thing, phytochemicals could induce ferroptosis to suppress the progression of liver fibrosis and HCC. For instance, magnesium isoglycyrrhizinate, derivatives of artemisinin (such as artemether, artesunate, and dihydro-artemisinin (DHA)), wild bitter melon extracts, chrysophanol, and zalkaloid berberine could block the development of liver fibrosis by triggering HSC ferroptosis [ 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 ]. Besides, several studies revealed that DHA could trigger ferroptosis to block HCC growth by promoting PEBP1/15LO formation or an unfolded protein response [ 153 , 154 ].…”
Section: Cell Death In Liver Diseasesmentioning
confidence: 99%